Konsep Pemikiran Ekonomi Dan Kebijakan Pasar Dalam Perspektif Yahya Bin Umar Dan Relevansinya Pada Sistem Ekonomi Modern - Suparno, Suparno; Mukhlishin, Ahmad (Universitas Islam Negeri Raden Intan Lampung, 2023)
This paper will explain the contribution of Yahya bin Umar's economic thinking regarding the role of the state in the economy in the market. Yahya bin Umar had contributed his thoughts in the 9th century AD. According to him, the role of the state in regulating the market and prices of goods was not very dominant, because the state intervened if in the mechanism of price of goods in the market experienced monopolistic practices such as ihtikar, cartels and hoarding of goods. So, the role of the state is indispensable for controlling prices and goods for the benefit and welfare of society. Keywords: thinking, market,,Ihtikar (hoarding of goods) Tasy'ir (pricing)